Influencia del Drawback, Saldo a Favor del Exportador en Situación Financiera y Económica empresa Agroexportadora Villaverde SAC Trujillo, 2014 - Sanchez Huaman, William Ricardo (2020)
ABSTRACT The problem of the present investigation is related to the study of the influence of Drawback and the Balance in Favor of the Exporter in the Financial and Economic Situation of the Agroexportadora Villaverde S.A.C. Trujillo district, with the objective of determining the influence of the drawback and the balance in favor of the exporter in the financial and economic situation of said company. The material used is the Company under study, based on the economic information for the months of May, June and July of 2014. The main result includes the treatment of said mechanism, Drawback in the company and its advantages in the financial order especially in liquidity, so its main conclusion is to have determined the advantages of Drawback and the Balance in Favor of the Exporter in this type of business.